Oxford Handbook of Human Action - Morsella, Ezequiel; Bargh, John A.; Gollwitzer, Peter M. (Oxford Oxford University Press, 2009)
In the last decade, there has been a tremendous surge of research on the mechanisms of human action. This volume brings together this new knowledge in a single, concise source, covering most if not all of the basic questions regarding human action: What are the mechanisms by which action plans are acquired (learned), mentally represented, activated, selected, and expressed? The chapters provide up-to-date summaries of the published research on this question, with an emphasis on underlying mechanisms.This 'bible' of action research brings together the current thinking of eminent researchers in the domains of motor control, behavioral and cognitive neuroscience, psycholinguistics, biology, as well as cognitive, developmental, social, and motivational psychology. It represents a determined multidisciplinary effort, spanning across various areas of science as well as national boundaries.
Keywords: Humanities